The Effect of Financial Socialization and Financial Attitude on Financial Management Behavior with Locus of Control as Mediating Variable (Case Study of ITB Yadika Pasuruan Management Study Program Student) - Rahayu, Sri Puji; Suriyok, Khamdan; Syaifudin, Arif; Ferdiansyah, Mohammad Arif; Al Fajar, Nur Farid (Journal of International Conference Proceedings, 2024)
In practice students also experience problems that are used as a phenomenon in this study, where based on the results of interviews students are able to save on their income but still experience financial problems in everyday life. Based on this phenomenon, this study was conducted to examine ‘The Effect of Financial Socialization and Financial Attitude on Financial Management Behavior with Locus of Control as a mediating variable’ The results of this study state that there is a significant influence between Financial Socialization on Financial Management Behavior (H1 accepted). Financial Socialisation has a significant effect on Locus of Control (H3 is accepted). Financial Attitude on Locus of Control (H4 is accepted). Locus of Control has a significant effect on Financial Management Behaviour (H5 is accepted). Locus of Control can mediate Financial Socialization on Financial Management Behavior (H6 accepted). On the other hand, this study also shows that Financial Attitude has no significant effect on Financial Management Behavior and Locus of Control is also unable to mediate Financial Attitude on Financial Management Behavior so it can be concluded that H2 and H7 are rejected